REFLECTIONS ON THE FUNCTIONAL APPROACH FOR THE ELDERLY AS AID TO DEFINE REQUIREMENTS IN PRODUCT DESIGN (Human Factors in Design, 2012)
The present article aims at approaching the main concepts that describe the research towards product design for the elderly, especially regarding the definition of project requirements. For this study, some concepts along with their authors ‘perspectives have been addressed: in the field of Biomechanics, ergonomics and anthropometry, distinguishing themselves respectively: Hamill (2010), Gomes (2003), Moraes e Mont´alvão (2003), lida (2005) and Panero (2002). For this theoretical framework the following concepts have also been taken into account:  Ely and Cavalcanti´s population ageing (2001), Pupo, Melo and Ferrés social inclusion, Analysis of Daily Living (ADL) by Barros (2009) and Matsudo (2004), as well as some studies directed towards the consumption pattern of the elderly. Beyond the theoretical approach, some tools for measuring the physical capability of the elderly in their analysis of daily living have been proposed, such as: TEMPA (Test d'Evaluation des Membres Supérieurs de Personnes Agées), Hand Grip Strength, Moberg´s Test, TUG (Time Up and Go) and the Berg balance scale.